2018
DOI: 10.18632/oncotarget.25388
|View full text |Cite
|
Sign up to set email alerts
|

Automated DNA extraction using cellulose magnetic beads can improve EGFR point mutation detection with liquid biopsy by efficiently recovering short and long DNA fragments

Abstract: The clinical utility of plasma DNA for detecting cancer-specific mutations has rapidly achieved recognition, but reliability has not been established because of relatively low mutation-detection rates compared with those from tissue re-biopsy. To address this shortcoming we examined efficiency, in terms of mutation detection, of an automated DNA extraction system that uses cellulose magnetic beads. A fully automated, highly sensitive point-mutation-detection method, mutation-biased PCR and quenching probe (MBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Chan, K. C. et al reported that repeated freeze-thaw cycles lead to fragmentation of cfDNA even if the DNA concentration does not change [ 34 ]. We recently demonstrated that cfDNA integrity is maintained after isolation using a silica membrane spin column [ 22 ]. This suggests that fragmentation of DNA occurs during long-term storage, leading to difficulty conducting PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chan, K. C. et al reported that repeated freeze-thaw cycles lead to fragmentation of cfDNA even if the DNA concentration does not change [ 34 ]. We recently demonstrated that cfDNA integrity is maintained after isolation using a silica membrane spin column [ 22 ]. This suggests that fragmentation of DNA occurs during long-term storage, leading to difficulty conducting PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pre-analytical procedures, including type of blood collection tube, choice of anticoagulant, centrifugation protocol, storage conditions, and DNA extraction method, should be reviewed. We recently reported that DNA extraction with cellulose magnetic beads produced higher recovery of cfDNA and better quality than with a silica membrane spin column system, leading to an improved efficiency of EGF R mutation detection [ 22 ]. However, assessment of other steps of pre-analytical procedures has not been made.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating free DNA (cfDNA) exists in peripheral blood and is derived from tumor cells and from normal cells (mainly lymphocytes). Recently, we reported that cfDNA was better isolated with cellulose magnetic beads for DNA capturing, and the amount of ctDNA was greater than that obtained with silica membrane spin columns [7]. Using the capillary electrophoresis system, we also demonstrated the existence of bimodal peaks, comprising long fragment cfDNA of 5Kb and short fragment cfDNA of 170bp.…”
Section: Introductionmentioning
confidence: 79%
“…Age prevalence of the tumor is among second and third decades [ 8 ]. Symptoms of the patients with JGCT are headaches, retinopathy, double vision, dizziness, nausea, vomiting, polyuria, and proteinuria [ 7 ]. Macroscopically, the tumor is yellow to tan and has fibrous capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Gene mutations were detected by mutation-biased PCR and quenching probe (MBP-QP) system using i-densy (IS-5320, ARKRAY Inc., Kyoto, Japan) [ 7 ]. DNA was extracted from 3 pieces of 5 μ m paraffin embedded tissue sample by using Maxwell 16® system (Promega Corporation, Tokyo, Japan) after proteinase K treatment (70°C, overnight).…”
Section: Methodsmentioning
confidence: 99%